1774. Ridinilazole (RDZ) for Clostridium difficile infection (CDI): Correlation of In Vitro Spectrum of Activity with Human Gut Microbiome Profiles from a Phase 2 Clinical Trial. (26th November 2018) - Vickers, Richard; Goldstein, Ellie J C; Citron, Diane; Snydman, David; Thorpe, Cheleste M; Kane, Anne V
Abstract: Background: Recurrence of CDI (rCDI) is associated with perturbation of the gut microbiome during treatment with vancomycin (VAN) or metronidazole (MTZ). RDZ is a novel, targeted spectrum antibacterial under investigation to treat CDI and reduce rCDI. Here correlation of in vitro spectrum of activity with preservation of the human gut microbiome and clinical outcomes is presented. Methods: Susceptibility testing was to CLSI standards with VAN, MTZ, and fidaxomicin (FDX) comparators. The Phase 2 clinical trial was a double-blind, randomized study of 100 patients assigned 1:1 to 10 days RDZ 200 mg BID or VAN 125 mg QID treatment. Primary endpoint was sustained clinical response (SCR), defined as cure at end of therapy (EOT), and no rCDI for the next 30 days. Relative effects of RDZ and VAN on the gut microbiome were examined by sequencing 16S rDNA amplicons from stool collected at baseline, days 5, 10, 25, and end of study. Bioinformatic analyses were performed in QIIME. Results: RDZ C. difficile ( N = 50) MIC range was 0.125–0.25 μg/mL. Clostridium spp. showed varied RDZ susceptibility; C. innocuum MIC90 1 μg/mL, C. ramosum and C. perfringens MIC90 >512 μg/mL. VAN showed potent to moderate growth inhibition of all Clostridium spp. (MIC range 1–16 µg/mL). Limited RDZ activity was observed for Gram-positive anaerobes, including Bifidobacteria, Eggerthella, Finegoldia, and Peptostreptococcus (MIC90 >512, >512, 64, and 64 μg/mL) compared with VAN (MIC90 1, 4, 0.5, and 0.5 μg/mL). Bacteroides fragilis MIC90 for RDZ and VAN were >512 and 64 µg/mL, respectively. These in vitro data correlate closely with human microbiome profiles. RDZ reduced C. difficile to below detection with other reductions in abundancy observed in only 2 families from the Clostridia . VAN at EOT resulted in significant losses, often below detection, in 4 Firmicutes families, Actinobacteria, and Bacteroidetes and a 25-fold increase in Proteobacteria abundance. The preservation of the microbiome by RDZ likely accounted for reduced rCDI compared with VAN with RDZ shown to be superior on SCR to VAN with rates of 66.7% and 42.4%, respectively (pre-specified 90% CI 3.1, 39.1). Conclusion: These data demonstrate strong translation of in vitro spectrum to human gut microbiome preservation during therapy and support further clinical development of RDZ. Disclosures: R. Vickers, Summit Therapeutics: Employee, Salary and Stock options. E. J. C. Goldstein, Summit Therapeutics: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient. D. Citron, Summit Therapeutics: Grant Investigator, Research grant. D. Snydman, Summit Therapeutics: Grant Investigator, Grant recipient. C. M. Thorpe, Summit Therapeutics: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient. A. V. Kane, Summit Therapeutics: Grant Investigator, Grant recipient.